Vitamin D levels and deficiency with different occupations: a systematic review - Sowah, Daniel; Fan, Xiangning; Dennett, Liz; Hagtvedt, Reidar; Straube, Sebastian (BMC public health, 2017)
Vitamin D deficiency is prevalent worldwide, but some groups are at greater risk. We aim to evaluate vitamin D levels in different occupations and identify groups vulnerable to vitamin D deficiency. An electronic search conducted in Medline, Embase, the Cochrane Central Register of Controlled Trials, and CINAHL Plus with Full Text generated 2505 hits; 71 peer-reviewed articles fulfilled the inclusion criteria. Occupations investigated included outdoor and indoor workers, shiftworkers, lead/smelter workers, coalminers, and healthcare professionals. We calculated the pooled average metabolite level as mean ± SD; deficiency/insufficiency status was described as % of the total number of subjects in a given category. Compared to outdoor workers, indoor workers had lower 25-hydroxyvitamin D (25-(OH)D) levels (40.6 ± 13.3 vs. 66.7 ± 16.7 nmol/L; p < 0.0001). Mean 25-(OH)D levels (in nmol/L) in shiftworkers, lead/smelter workers and coalminers were 33.8 ± 10.0, 77.8 ± 5.4 and 56.6 ± 28.4, respectively. Vitamin D deficiency (25-(OH)D < 50 nmol/L), was high in shiftworkers (80%) and indoor workers (78%) compared to outdoor workers (48%). Among healthcare professionals, medical residents and healthcare students had the lowest levels of mean 25-(OH)D, 44.0 ± 8.3 nmol/L and 45.2 ± 5.5 nmol/L, respectively. The mean 25-(OH)D level of practising physicians, 55.0 ± 5.8 nmol/L, was significantly different from both medical residents (p < 0.0001) and healthcare students (p < 0.0001). Nurses and other healthcare employees had 25-(OH)D levels of 63.4 ± 4.2 nmol/L and 63.0 ± 11.0 nmol/L, respectively, which differed significantly compared to practising physicians (p = 0.01), medical residents (p < 0.0001) and healthcare students (p < 0.0001). Rates of vitamin D deficiency among healthcare professionals were: healthcare students 72%, medical residents 65%, practising physicians 46%, other healthcare employees 44%, and nurses 43%. Combined rates of vitamin D deficiency or insufficiency (25-(OH)D < 75 nmol/L) were very high in all investigated groups. Potential confounders such as gender and body composition were not consistently reported in the primary studies and were therefore not analyzed. Furthermore, the descriptions of occupational characteristics may be incomplete. These are limitations of our systematic review. Our review demonstrates that shiftworkers, healthcare workers and indoor workers are at high risk to develop vitamin D deficiency, which may reflect key lifestyle differences (e.g. sunlight exposure). This may help target health promotion and preventive efforts.